CD25-targeted antibody–drug conjugate depletes regulatory T cells and eliminates established syngeneic tumors via antitumor immunity. Issue 2 (10th September 2020) - Zammarchi, Francesca; Havenith, Karin; Bertelli, Francois; Vijayakrishnan, Balakumar; Chivers, Simon; van Berkel, Patrick H
Abstract : Background: Regulatory T cells (Tregs ) contribute to an immunosuppressive tumor microenvironment. They play an important role in the establishment and progression of tumors with high Tregs infiltration and present a major obstacle to tumor eradication by immunotherapies. Numerous strategies have been attempted to deplete or block Tregs, although their success has been limited. Methods: A CD25-targeted, pyrrolobenzodiazepine (PBD) dimer-based antibody–drug conjugate (ADC) was investigated for its ability to deplete Tregs and induce antitumor immunity. Antitumor activity of CD25-ADC either alone or in combination with an anti-programmed cell death protein 1 (PD-1) antibody was evaluated in CD25-negative syngeneic models that exhibit tumor infiltration of CD25-expressing Tregs, and its pharmacodynamics and pharmacokinetics were assessed. Results: Single low doses of CD25-ADC resulted in potent and durable antitumor activity in established syngeneic solid tumor models and the combination of a suboptimal dose was synergistic with PD-1 blockade. Tumor eradication by the CD25-targeted ADC was CD8+ T cell-dependent and CD25-ADC induced protective immunity. Importantly, while CD25-ADC mediated a significant and sustained intratumoral Tregs depletion, accompanied by a concomitant increase in the number of activated and proliferating tumor-infiltrating CD8+ T effector cells, systemic Tregs depletion was transient, alleviating concerns of potential autoimmune side effects. Conclusions: This study shows that a PBD dimer-based, CD25-targeted ADC is able to deplete Tregs and eradicate established tumors via antitumor immunity. This represents a novel approach to efficiently deplete Tregs via a very potent DNA damaging toxin known to induce immunogenic cell death. Moreover, this study provides proof of concept for a completely new application of ADCs as immunotherapeutic agents, as the main mode of action relies on the ADC directly targeting immune cells, rather than tumor cells. These strong preclinical data warrant the clinical evaluation of camidanlumab tesirine (ADCT-301), a PBD-based ADC targeting human CD25, either alone or in combination with checkpoint inhibitors in solid tumors with known Tregs infiltration. A phase I trial (NCT03621982 ) of camidanlumab tesirine in patients with selected advanced solid tumors is ongoing.